Throughput enhancement for fixed WiMAX network using distributed model - Lawal, I.A. (Institute of Electrical and Electronics Engineers Inc., 2014)
Recently, broadband wireless communication serves as one of the most growing and developing technology in the field of telecommunications. The broadband provides multimedia services for voice, video, High Definition TV (HDTV), and games with certain Quality of Service (QoS). For these services, a high data transmission is greatly needed. Worldwide Interoperability for Microwave Access (WiMAX) Network aims to provide this QoS with high data rate and throughput. However the existing WiMAX architecture does not provide sufficient QoS. In this regard, a Distributed Master-Slave Model was developed to improve QoS with respect to throughput in the Fixed WiMAX Network in order to evaluate the throughput performance for the delivery of better services to the end users. The new model was simulated in OPNET modeler 16.0 with introduction Master Base Stations (BSs) using Orthogonal Frequency Division Multiplexing (OFDM) techniques and compared with the existing model which is centralized using Frequency Division Multiplexing (FDM) techniques. The proposed model throughput results obtained show that the proposed model has better results as compared with the existing model. Â© 2014 IEEE.